10.1142/9789814343060 (CrossRef Listing of Deleted DOIs, 2000)
Alzheimer's disease (AD), a progressive neurodegenerative disease with a rising global prevalence, is characterized by amyloid-β (Aβ) aggregation, tau hyperphosphorylation, inflammation, oxidative damage, and neuronal apoptosis. Studies have increasingly recognized epigenetic modifications as key regulators in the development of AD. Epigenetic modifications, particularly histone acetylation, are increasingly recognized as critical regulators of cell survival and AD pathogenesis. Although artemisinin (ART) exhibits potent anti-oxidative, anti-inflammatory, and neuroprotective properties, its impact on histone acetylation in AD remains uncharacterized. This study investigated whether ART regulates histone acetylation to confer neuroprotection and rescue behavioral deficits in Alzheimer's disease models. Using SH-SY5Y cells, primary neurons, and 3xTg-AD mice, we found that ART restores histone acetylation homeostasis by enhancing histone H4 acetylation. Mechanistically, this effect is driven by the activation of the CaMK IV/PKA-CREB signaling cascade. Treatment with ART reduced ROS, improved mitochondrial function, decreased Aβ1-42 deposition, and suppressed neuronal apoptosis. However, these beneficial effects were abolished by PKA or CaMK IV inhibitors. Consequently, ART treatment significantly reduced reactive oxygen species (ROS) generation, restored mitochondrial function, decreased Aβ1-42 deposition, suppressed neuronal apoptosis, and alleviated AD-like neuropathology and cognitive deficits. Crucially, the neuroprotective and epigenetic benefits of ART were entirely abolished by pharmacological inhibitors of PKA or CaMK IV. This study is the first to demonstrate that artemisinin ameliorates AD pathology and behavioral impairments via the CaMK IV/PKA-CREB-Ace-H4 axis, establishing ART as a promising therapeutic candidate for epigenetic intervention in AD.